Where is the Money Coming From? Ten Stylized Facts on Financing Social Protection Responses to COVID-19 - Almenfi, Mohamed (World Bank, Washington, DC, 2020)
The unprecedented and ongoing scale-up of social protection responses to the COVID-19 pandemic dwarf the response to the Great Recession. But how are countries financing such scale-up efforts? This note lays out ten stylized findings from a rapid review of social protection financing sources in thirty-one countries, including in terms of composition between external and domestic resources, and specific modalities within each.